Condensin II Alleviates DNA Damage and Is Essential for Tolerance of Boron Overload Stress in Arabidopsis([W]) - Sakamoto, Takuya (American Society of Plant Biologists, 2011)
Although excess boron (B) is known to negatively affect plant growth, its molecular mechanism of toxicity is unknown. We previously isolated two Arabidopsis thaliana mutants, hypersensitive to excess B (heb1-1 and heb2-1). In this study, we found that HEB1 and HEB2 encode the CAP-G2 and CAP-H2 subunits, respectively, of the condensin II protein complex, which functions in the maintenance of chromosome structure. Growth of Arabidopsis seedlings in medium containing excess B induced expression of condensin II subunit genes. Simultaneous treatment with zeocin, which induces DNA double-strand breaks (DSBs), and aphidicolin, which blocks DNA replication, mimicked the effect of excess B on root growth in the heb mutants. Both excess B and the heb mutations upregulated DSBs and DSB-inducible gene transcription, suggesting that DSBs are a cause of B toxicity and that condensin II reduces the incidence of DSBs. The Arabidopsis T-DNA insertion mutant atr-2, which is sensitive to replication-blocking reagents, was also sensitive to excess B. Taken together, these data suggest that the B toxicity mechanism in plants involves DSBs and possibly replication blocks and that plant condensin II plays a role in DNA damage repair or in protecting the genome from certain genotoxic stressors, particularly excess B.